ANALYSIS OF HEALTH FINANCING PRINCIPLES IN SUPPORTING UNIVERSAL HEALTH COVERAGE IN INDONESIA: LITERATURE REVIEW - Pribadi, Frita Ayu (Journal of Public Health Research and Community Health Development, 2024)
Background: Health financing is one of the focuses in the National Health System Reform major project in the 2022 Government Work Plan. However, obstacles have been found in health financing in Indonesia, including a lack of promote and preventive financing; less non-governmental involvement; and weak development of national health insurance (JKN) services. Purpose: To understand the principles of health financing for the realization of universal health coverage. This principle uses the concept of Kutzin et al (2017) and Atim et al (2021), namely revenue raising; pooling revenues; purchasing services; benefit design and rationing mechanism; and governance and institutional arrangements, including decentralization. Method: Focuses on the principles of health financing by utilizing secondary data sources through qualitative methods. The data sources were obtained from scientific journals, official government reports, related web pages, and others. Results: The effectiveness of increasing income for health financing cannot yet be measured. Revenue collection was found to overlap with health financing sources. There was a deficit for the JKN budget, and the community was not disciplined in paying contributions in purchasing services and distribution mechanisms. For the principle of decentralization, regional governments still depend on the central government in planning and budgeting health financing. Conclusion: The principles of health financing in Indonesia are not yet optimal in practice. This article contributes to looking at the gaps in information regarding the government's commitment to universal health coverage.